Ability of the Central Sensitization Inventory to Identify Central Sensitivity Syndromes in an Outpatient Chronic Pain Sample. Issue 4 (April 2015) - Neblett, Randy; Hartzell, Meredith M.; Cohen, Howard; Mayer, Tom G.; Williams, Mark; Choi, YunHee; Gatchel, Robert J.
Abstract : Objectives: The aim of this study was to determine the ability of the central sensitization inventory (CSI), a new screening instrument, to assist clinicians in identifying patients with central sensitivity syndromes (CSSs). Methods: Patients from a psychiatric medical practice (N=161), which specialized in the assessment and treatment of complex pain and psychophysiological disorders, were assessed for the presence of a CSS. CSI scores, using a previously determined cutoff of "40" of "100, " were compared between the CSS patient group (n=99) and the non-CSS patient group (n=62). Information on false positives, false negatives, true positives, and true negatives were analyzed, and sensitivity and specificity analyses were conducted. In addition, CSS-relevant variables such as depression, abuse, and substance abuse were examined. Results: A large percentage of CSS patients had comorbid major depressive disorder (80%) and abuse history (43%), which was higher than rates for the patients without a CSS (55% and 24%, respectively). The CSI correctly identified 82.8% (n=82) of CSS patients as having a CSS (ie, sensitivity) and 54.8% (n=28) of non-CSS patients as not having a CSS (ie, specificity). False-positive patients (not diagnosed with a CSS, but scoring >40 on the CSI) reported more severe pain, interference in daily functioning, and abuse history, compared with the non-CSS patients who scored below 40 (ie, true negatives). Conclusions: The CSI is a useful and valid instrument for screening patients for the possibility of a CSS, although the chances of false positives are relatively high when evaluating patients with complex pain and psychophysiological disorders.